THE LINGUO-STYLISTIC ANALYSIS OF THE WORD 'HEART' IN ENGLISH LANGUAGE BASED ON THE NOVEL “PRIDE AND PREJUDICE” (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This literary-linguistic study examines how Jane Austen employs metaphorical and idiomatic uses of “heart” in “Pride and Prejudice” to shape characterization, convey narrative irony, and reinforce key themes in the novel. Adopting a cognitive metaphor framework, the analysis identifies multiple distinct conceptual metaphors for “heart” (e.g., heart as the seat of emotion, heart as an object to be won in love, sincerity as wholeheartedness, and heart versus head conflict) and also demonstrates how these figurative expressions enrich the novel’s narrative nuance and thematic depth. Characters use “heart” metonymically to denote emotional capacity or courage (“heart enough” for love), and idioms like “with all my heart” can signal genuine feeling or, in ironic contexts, its absence. By leveraging everyday heart metaphors (such as love conceptualized as a battle for hearts), Austen distinguishes authentic emotion from performative social courtesy, underscoring themes of emotional integrity, sincerity, and the balance between sentiment and reason.